PARTISIPASI WANITA NELAYAN DALAM PENGELOLAAN LINGKUNGAN WILAYAH PESISIR KABUPATEN BANTUL - Suyoto, Rahmat Slamet; Anggraini, Oktiva (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2016)
Efforts to environmental conservation and management of fisheries products tend to focus on fishing compared with the chain of local values relating to the economy and the labor market. The participation of women fishers more often underappreciated. This study aims to determine the participation of women in the fishing and marine fisheries management in Bantul, with a qualitative approach, method of interview, observation, focus group discussions and documentation. The study took purposively selected locations on the coast and coastal New Depok Parangtritis, Bantul. The results showed a number of examples of environmental conservation programs fishermen ruled out the role of women in the planning, implementation and evaluation of programs. Women devote more time fishing on their domestic responsibilities, livelihood diversification choice more often limited. This limitation is exacerbated by the lack of education. Becomes important, when the purpose of development in line with environmental management and profitable position of women in environmental management. Because of this, awareness and participation of tourism stakeholders including women fishing is very needed in sustainable environmental management. This participation from the planning, implementation, evaluation of the benefit received by women fishers. Participation which originally symbolic of the study sites can be developed with intensive mentoring extension of the activities of women's groups of fishermen manifest into independent participation. Collective action fisher woman other than as a means of gathering, enriching also useful as an alternative source of business capital. Through the activities of formal, informal them, toma and extension convey the importance of preserving the environment. Efforts to add events, travel and travel product diversification initiated by the government and the private sector are expected to increase the participation of women fishing and sustainable environmental management. Keywords: women fishing, environment, participation.